Evaluation of the aortic valve gradient in the patients with stentless 3F bioprothesismade of equine pericardium – one year follow-up - Bartuś, Krzysztof; Sadowski, Jerzy; Kapelak, Bogusław; Myć, Jacek; Bartuś, Stanisław; Oleś, Krzysztof; Filip, Grzegorz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background: The acute result of surgical replacement of aortic valve is reduction of the transvalular gradient. The aim of the study was evaluation of the aortic valve gradient in one year follow-up (FU) of the patients with left ventricle hypertrophy after equine pericardial stentless bioprothesis replacement (3F Therapeutics, Lake Forest, USA, Medtronic, Inc., Minneapolis, USA). Material and methods: 40 patients with left ventricle hypertrophy [8 women and 32 men aged 23-78, mean 57 (± SD 10.2)] qualified to aortic valve replacement. Ultrasound evaluation of the gradient was performed in 1; 3-6 and 11-14 month FU after surgery. Results : Mean and maximal gradients were: 8.6 mmHg (± SD = = 4.8) and 16.1 mmHg (± SD = 8.8) after procedure, after 3-6 months FU were 7.8 mmHg (± SD = 3.7) and 14.5 mmHg (± SD = 7), 7.7 mmHg (± SD = 2.8) and 14.4 mmHg (± SD = 5.2) 11-14 months FU. Conclusions : Mean gradient and maximal gradient were low and there were no statistically significant changes during 1-year FU in comparison to baseline values.